Permintaan Buah Pisang Ambon Oleh Rumah Tangga Di Kecamatan Denpasar Barat, Kota Denpasar, Provinsi Bali - Antara, Made; Wirawan, I Gede Yono (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 1, Februari 2013 (pp. 1-70), 2013)
This study aims to determine the function of green banana fruit demand, factors that affect the demand for green banana fruit and banana fruit elasticity of demand in the district of West Denpasar. Purposive selection of sites is done at the West Pemecuatan Vilage, West Padangsambian Village and Tegal Harum Village.  Populai this study were all households in three villages and a sample taken amounted to 90 households with a random sampling technique. This study used two models of analysis of the Cobb-Douglas Demand Functions and Linear Demand Functions, using the criteria of economics, econometrics and statistics, namely, R2, F-test and t-test, then obtained a model of the demand function for the set as a model of a representative demand function represents the study area are used for forecasting.Free variable in the function of green banana fruit demand by households is X1 = price of banana fruit,  X2 = the price of fruit other than bananas fruit, X3 = total household income, X4 = number of household members, X5 = mother's formal education level of the home ladder, and D (dummy variables) = head of household jobs.  The results show the function of green banana fruit demand by households tha representative is the linear demand function, nemaly: Y = 0,7285792 – 0,00003636X 1 + 0,00014478X 2 + 0,00000110X 3 + 0,19004321X 4 + 0,60582075X 5 + 0,04631297D.  Factors that influence the demand for banana fruit by the domestic price of other fruit, household income, number of household members, and educational level of the housewife. The price elasticity of demand for banana fruit by households is inelastic, the income elasticity indicates that the fruit, including bananas in the category of normal goods, other fruits (papaya, watermelon, oranges, and mangoes) can be considered as substitutes of banana fruit by the analysis of cross-price elasticity.
Keywords: demand; green banana; west denpasar; elasticity